Trypanosoma cruzi surface mucins with exposed variant epitopes - Pollevick, G.D. (2000)
The protozoan parasite Trypanosoma cruzi, the agent of Chagas disease, has a large number of mucin molecules on its surface, whose expression is regulated during the life cycle. These mucins are the main acceptors of sialic acid, a monosaccharide that is required by the parasite to infect and survive in the mammalian host. A large mucin-like gene family named TcMUC containing about 500 members has been identified previously in T. cruzi. TcMUC can be divided into two subfamilies according to the presence or absence of tandem repeats in the central region of the genes. In this work, T. cruzi parasites were transfected with one tagged member of each subfamily. Only the product from the gene with repeats was highly O-glycosylated in vivo. The O-linked oligosaccharides consisted mainly of β-D-Galp(1→4)-GlcNAc and β-D-Galp(1→4)[β-D-Galp(1→6)]-D-GlcNAc. The same glycosyl moieties were found in endogenous mucins. The mature product was anchored by glycosylphosphatidylinositol to the plasma membrane and exposed to the medium. Sera from infected mice recognized the recombinant product of one repeats-containing gene thus showing that they are expressed during the infection. TcMUC genes encode a hypervariable region at the N terminus. We now show that the hypervariable region is indeed present in the exposed mature N termini of the mucins because sera from infected hosts recognized peptides having sequences from this region. The results are discussed in comparison with the mucins from the insect stages of the parasite (Di Noia, J. M., D'Orso, I., Sanchez, D. O., and Frasch, A. C. C. (2000) J. Biol. Chem. 275, 10218-10227) which do not have variable regions.